Influence of Leadership and Communication on the Performance of South Jakarta District Court Employees - Martin, Reynaldo; Arifin, Antoni Ludfi (Dinasti Publisher, 2025)
This study examines the influence of leadership, communication on employee performance at the South Jakarta District Court. The author highlights the importance of synergy between competent human resources and effective work systems to achieve organizational goals. Employee performance is influenced by good leadership and effective communication, where lack of understanding of tasks can hinder coordination and target achievement. This study uses qualitative methods, focusing on collecting descriptive data to describe existing conditions. The results of the study indicate that effective leadership and good communication can improve employee motivation and performance.